2014
DOI: 10.1007/s10522-014-9497-0
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes of nuclear morphology are uncoupled from longevity in Caenorhabditis elegans IGF/insulin receptor daf-2 mutants

Abstract: Nuclear envelope (NE) architecture and aging have been associated since the discovery that certain human progeria diseases are due to perturbations in processing of lamin A protein, generating alterations in NE morphology. However, whether changes in the NE are a causal effect of normal and premature aging is still controversial. Caenorhabditis elegans is a model organism where observations supporting both, dependent and independent roles of nuclear architecture in the aging process, have been reported.Using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
(33 reference statements)
3
10
0
Order By: Relevance
“…This suggests that altered nuclear morphology and longevity can be uncoupled, and that changes in nuclear shape are not the main driver of aging. A similar conclusion was reached by Pérez-Jiménez et al (2014), who found that in daf-2 mutant worms grown at 20°, which have increased longevity, irregular nuclear morphology occurred at the same age as in wild-type worms.…”
Section: Nuclear Morphology During Agingsupporting
confidence: 78%
See 1 more Smart Citation
“…This suggests that altered nuclear morphology and longevity can be uncoupled, and that changes in nuclear shape are not the main driver of aging. A similar conclusion was reached by Pérez-Jiménez et al (2014), who found that in daf-2 mutant worms grown at 20°, which have increased longevity, irregular nuclear morphology occurred at the same age as in wild-type worms.…”
Section: Nuclear Morphology During Agingsupporting
confidence: 78%
“…Moreover, the repressive H3K27me3 modification is lost as cells age (Jin et al 2011). As discussed above, the nucleus of aging worms undergoes morphological changes reminiscent of aging cells in mammals, although the two phenomena can be genetically uncoupled (Pérez-Jiménez et al 2014). The link in C. elegans between nuclear morphology in aging cells and gene expression is not known: does altered nuclear morphology affect the ability of chromatin to associate with the nuclear periphery, and if so, does that lead to changes in gene expression that affect the aging process?…”
Section: Changes In Chromosome Organization During Developmentmentioning
confidence: 99%
“…Post-translational modifications of DAF-16 include its phosphorylation by AMPK ( 70 ). AMPK modulation of lifespan has been shown to occur also via CREB-regulated transcriptional coactivators in response to low levels of energy ( 35 ) ( Figure 1 ).…”
Section: Transcriptional Regulators and Epigenetic Regulation In mentioning
confidence: 99%
“…The exact cellular and molecular mediators responsible for integrating these two extreme metabolic states of obesity and caloric restriction to immune function are beginning to be revealed. A perturbation of the IGF/insulin signaling cascade is known to increase longevity in C. elegans, which appears to be mediated though metabolic effects at the systemic level [80]. Of note, PHB promotes longevity in C. elegans, depending on metabolic status and genetic background [37], and PHB modulates insulin signaling in a phosphorylation-dependent manner [8,81].…”
Section: Box 1 Phb: a Potential Candidate In Integrating Metabolic Amentioning
confidence: 99%